Over the steamy swamp - Geraghty, Paul, 1959- (San Diego : Harcourt Brace, 1989)
A hungry mosquito starts a food chain in a steamy swamp as each hungry animal both preys and is preyed upon.
"A Voyager book.".
School Library Journal, October 2001.
School Library Journal.
3.8
K-3
Keywords: Food chains (Ecology) -- Juvenile literature; Swamp animals -- Juvenile literature; Swamp ecology -- Juvenile literature; Swamp animals; Swamp ecology; Food chains (Ecology); Food chains (Ecology); Swamp animals; Swamp ecology; Food chains (Ecology).; Swamp ecology; Integrated Ed -- Humanities -- Level AK